IMPROVING STUDENTS’ ENGLISH VOCABULARY MASTERY THROUGH TOTAL PHYSICAL RESPONSE METHOD AT GRADE VII A OF MTs Negeri 2 KUANTAN SINGINGI SENTAJO RAYA DISTRICT - KUANTAN SINGINGI REGENCY - Elda Wati (J-Shelves of Indragiri (JSI), 2021)
Vocabulary is essential in learning English because vocabularies are the key to producing English sounds, words, and sentences. In reality, students still had lack of English vocabulary mastery. One method to solve this problem is by applying Total Physical Response (TPR). This research was carried out at grade VII A of MTs Negeri 2 Kuantan Singingi Sentajo Raya district in Kuantan Singingi Regency. It is designed as Classroom Action Research. The research aims to know how far the Total Physical Responses can improve the students’ English vocabularies mastery. Data collection methods are observation and test. This is the test in multiple choices. Data analysis is quantitative, which got from the result of the test. The result of this research is that TPR could increase the students’ vocabulary. The students’ rate in pre-test is 40.00 %, the rate result in the first cycle is 54.54 %, .while in the rate result in the second test is 82.06. the final rate result in the third cycle is 90.00. Total Physical Response can improve students' English vocabularies at grade VII A in MTs Negeri 2 Kuantan Singingi.